Bioconversion of empty fruit bunches (EFB) and palm oil mill effluent (POME) into compost using Trichoderma virens - R., Dayana Amira; A. R., Roshanida; M. I., Rosli; M. F., Siti Fatimah Zahrah; J., Mohd Anuar; C. M., Nazrul Adha (Academic Journals, 2011)
This study shows the performance of Trichoderma virens as an activator for conversion of empty fruit bunches (EFB) and palm oil mill effluent (POME) into compost. EFB and POME are two abundant wastes produced by oil palm industries which keep accumulating. Since there is no proper way to dispose these wastes, a potential way is to turn them into value-added product which is compost. However, normal composting will take about 4 to 6 months and additional pure fungi on compost can reduce the time to only 21 to 45 days. It also promotes plant growth and fight plant diseases. T. virens is one of the potential fungus activator and the enzyme production by this specific fungus has been studied. Biodegradation of EFB and POME supplemented with T. virens and organic N (chicken manure) gave significant changes as compared to EFB and POME alone. Application of T. virens resulted in higher xylanase and cellulase activities which lead to rapid degradation of cellulose and hemicelluloses. Compost with T. virens has higher xylanase activity on day 36 which is 4.43 mol/(min.mg) as compared to the control which has 3.48 mol/(min.mg). The cellulase activity is 13.214 FPU/mg and 11.314 FPU/mg for compost with T. virens and compost without bioinoculant on day 36, respectively. The N, P, K content of compost with T. virens increased significantly after maturation which is 1.304, 0.5034 and 0.645%, respectively. This result shows that T. virens played a great role by shortening the composting period of EFB and POME while producing nutrient-enriched compost.